School Principal's Leadership Management in Developing Teacher Professionalism - Lyadi, Muslim; Syaifuddin, Muhammad; Afandi, Muslim (Journal of Practice Learning and Educational Development, 2026)
This article presents a research study on the leadership management of school principals in developing teacher professionalism. The aim of this article is to investigate the leadership management of school principals in developing teacher professionalism at Al Falaah Integrated Islamic Elementary School in Rengat, Indragiri Hulu. The research method used is qualitative research, conducted directly in the field. Data collection techniques were carried out through observation at the research location, direct interviews with the school principal, and literature studies. The research results show that the leadership management of the school principal in developing teacher professionalism at Al Falaah Integrated Islamic Elementary School in Rengat, Indragiri Hulu, has been well implemented. The school principal develops teacher professionalism through several management functions, including planning, organizing, directing, and supervising. By developing teacher professionalism, the school principal can identify training needs, arrange capacity-building programs, and evaluate teacher development outcomes regularly, create a conducive work environment, provide motivation, and ensure that each teacher has a fair opportunity to develop according to their potential.